Globalization and localization in advertising translation: a love-hate relationship? - Cristina Valdés Rodríguez (Revista de Lenguas para Fines Específicos, 2016)
The aim of this paper is to analyse how globalization has affected the activity of advertising translation, paying heed to how globalization and localization approaches integrate translation as a strategy to promote different kinds of products and in different media. A theoretical introduction will be provided on the intercultural and interdisciplinary nature of advertising and more precisely of advertising translation, also dealing with notions like institutional norms or with the well-known expression “Think globally, act locally”. Recent examples from printed campaigns, television spots and promotional material from several websites will be analysed to show how translation reveals the contradictions and principles inherent to globalization, and the tensions, or lack of them, between globalising and localising strategies, trying to reveal signs of homogenisation of cultural beliefs, customs and images, through the detailed analysis of a global product being promoted in local markets, and of a local brand aiming at becoming international.